Haematological Changes in Peripheral Blood of HIV Infected Persons with Correlation to CD4 Cell Count (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Objective: Aims at recognizing the haematological abnormalities in peripheral blood associated with HIV infection and to correlate the haematological abnormalities with CD4 cell count to highlight these manifestations with disease progression.Methodology: Observational cross sectional study.Setting: Department of Haematology, Armed Forces Institute of Pathology (AFIP), Dhaka cantonment.Patients: Two hundred four (204) HIV infected patients receiving antiretroviral therapy aged from three years to 65 years. There were 132 male and 72 female patients.Results: Anaemia was found in 103 (50.5%) cases. Leucopenia and thrombocytopenia were observed in ten (4.9%) and seven (3.4%) cases respectively. Lymphopenia was found in 12 (5.9%) cases. In 50 (24.5%) cases Erythrocyte Sedimentation Rate (ESR) was > 20 mm at the end of 1st hour. Flow cytometric analysis for CD4 cell count showed < 200 cells/cmm in 65 (31.8%) cases, in between 200 cells/cmm and 499 cells/cmm in 117 (57.4%) cases and > 500 cells/cmm in 22 (10.8%) cases.Conclusion: Haematological abnormalities are common in HIV infected patients and responsible for significant morbidity and mortality in these patients. These abnormalities are more frequent with disease progression. The present study revealed a significant increase in the number of anaemia, leucopenia, lymphopenia and thrombocytopenia with decreasing CD4 cell count.J Bangladesh Coll Phys Surg 2014; 32: 130-136